Analisis Perbandingan Kerangka Hukum untuk Keamanan Siber dan Perlindungan Data antara Vietnam dan Indonesia - Tri Nguyen Minh; Tram Ho Tran Bao (PT. Data Jaringan Visual Indonesia (Djava), 2026)
This study examines the comparative legal frameworks governing cybersecurity and personal data protection in Vietnam and Indonesia within the context of rapid digital transformation in Southeast Asia. As digital economies expand and internet penetration increases, both countries face growing cyber threats and complex challenges related to data governance, privacy protection, and national security. The research aims to identify the similarities and differences in the legal approaches adopted by Vietnam and Indonesia in regulating cybersecurity and data protection. The study employs a normative legal research approach combined with comparative legal analysis. Primary data consist of legal documents, including laws, decrees, and government regulations related to cybersecurity and personal data protection in both countries. Secondary data include academic literature, scholarly journal articles, and international reports discussing digital governance and cybersecurity policy in Southeast Asia. The data are analyzed using qualitative descriptive methods to identify regulatory characteristics, institutional structures, and enforcement mechanisms. The findings show that Vietnam adopts a centralized and security-oriented governance model emphasizing national security, political stability, and strong state control over cyberspace. In contrast, Indonesia implements a more decentralized and rights-based regulatory framework influenced by international standards such as the European Union’s General Data Protection Regulations (GDPR), focusing on personal data protection and digital economic integration.